Microlearning in Bahasa Indonesia : Potential and Challenges in Facing The Bored Generation Z - Ningrum, Chearen Asta Triyana; Ridwan, Muhammad Hasbullah (Universitas Pendidikan Mandalika, 2025)
This research aims to explore the potential and challenges of implementing microlearning in Indonesian as a learning method that suits the needs of Generation Z. The research used a descriptive qualitative approach involving 60 participants, consisting of university students and high school students in the Banyuwangi area, selected through a purposive sampling technique. Data were collected through in-depth interviews, questionnaires, and direct observation, then analyzed using thematic analysis and descriptive statistics. The results showed that microlearning has great potential in increasing Generation Z's learning engagement. As many as 80% of participants felt that short learning sessions helped them stay focused, while another 85% liked the flexibility offered by microlearning platforms. Observations also showed high engagement when interactive media such as quizzes and short videos were used. However, the study also uncovered some key challenges, including difficulties in simplifying complex material, internet access constraints in remote areas, and the need for greater learning independence. The discussion highlighted the importance of training educators to develop effective microlearning materials, technological solutions to overcome the digital divide, and the integration of gamification strategies to increase learning motivation. In addition, the development of Indonesian-based microlearning content is a great opportunity to increase the relevance of learning. This research concludes that with the right adaptation and support, microlearning can be an innovative learning solution for Generation Z in the digital era.